Conductive composition, and conductor, laminate structure, and electronic component using the same
A conductive composition using a water-soluble thermoplastic resin and a block copolymer addresses the challenges of providing elasticity and easy removal for wearable devices, achieving effective electrical conductivity and processability.
Patent Information
- Application Number
- JP2020154058
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-14
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2040-09-14
AI Technical Summary
Conductive compositions used in wearable devices require both elasticity and the ability to be easily peeled off from base materials, but existing solutions, such as those using water-soluble thermosetting resins, fail to provide sufficient elasticity and are difficult to remove by washing with water.
A conductive composition comprising a water-soluble thermoplastic resin and a block copolymer, which allows the conductor to be dissolved in water and easily peeled off from the base material, while maintaining the necessary electrical conductivity and elasticity for wearable devices.
The proposed conductive composition achieves excellent elasticity and electrical conductivity, enabling it to withstand the expansion and contraction of wearable devices without cracking, and can be easily removed from base materials by washing with water, thus improving processability and reducing material costs.
Smart Images

Figure 0007659376000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive composition, a conductor formed by solidifying the conductive composition, a laminated structure having a layer of the conductor, and an electronic component having the conductor or the laminated structure. [Background technology]
[0002] A paste-like conductive composition in which a metal powder is mixed with an organic binder is used as a material for forming a patterned conductor such as an electrode of a printed wiring board or the like. According to a conventional conductive composition, a desired conductor can be formed by applying the composition in a pattern and then solidifying it, but the obtained conductor generally has high hardness. Therefore, for flexible printed wiring boards, a conductive composition is required in which the solidified conductor has bending resistance.
[0003] Furthermore, with the recent growth of the wearable device field, there is a demand for imparting elasticity to conductors. In particular, the higher the degree of adhesion to the body of a wearable device, the higher the degree of elasticity required. In response to such demands, for example, a conductive composition has been proposed that uses an elastomer as an organic binder containing metal powder, thereby imparting not only flexibility but also elasticity to the conductor (Patent Document 1, etc.).
[0004] On the other hand, in wearable devices, since the materials used in the wiring and electrodes are expensive, attempts are being made to reuse them, and there is a demand for a technology to easily peel and recover the conductor from the base substrate. From the viewpoints of cost and environmental burden, washing with water is considered to be the most desirable method for peeling the conductor from the base substrate, but the conductive composition proposed in Patent Document 1 and the like is not soluble in water, and it is difficult to peel it from the base substrate by washing with water.
[0005] Incidentally, Patent Document 2 proposes that in a conductive composition capable of forming an electrode by screen printing, a water-soluble thermosetting resin is used as a binder resin, and water that dissolves the resin is used in combination with a dihydric alcohol solvent, so that printing tools, containers, etc. to which the conductive composition is attached can be removed by washing with water. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2015 / 005204 Brochure [Patent Document 2] Japanese Patent Application Publication No. 9-282937 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the conductive composition using the water-soluble thermosetting resin as a binder described in Patent Document 2, the elasticity of the obtained conductor is insufficient, and the conductor cannot follow when the wearable device expands and contracts, resulting in cracks and a significant increase in resistance. In addition, the conductive composition using the water-soluble thermosetting resin as a binder is water-soluble before solidification, but is insoluble in water in the solidified state (when the solvent has evaporated), and it is considered difficult to peel the conductor from the base substrate. Furthermore, the conductive composition described in Patent Document 2 contains water for dissolving the water-soluble thermosetting resin, and the water in the composition evaporates during the device production process, causing a deterioration in fluidity, and continuous printability and processability are significantly reduced.
[0008] Therefore, there is a demand for conductive compositions that are soluble in water even when they are conductors (solidified conductive compositions), and that can be easily peeled off from the base substrate by washing with water, making it possible to obtain conductors that combine the conductivity and elasticity required for wearable devices, and that have excellent continuous printability and processability required for device manufacturing processes.
[0009] Therefore, an object of the present invention is to provide a conductive composition which, even when solidified to form a conductor, dissolves in water and can be easily peeled off from the underlying substrate by washing with water, can give a conductor having both the conductivity and elasticity required for a wearable device, and has excellent continuous printability and processability required for the device manufacturing process.
[0010] Another object of the present invention is to provide a conductor obtained by solidifying such a conductive composition, a laminate structure having a layer of the conductor, and an electronic component having the conductor or the laminate structure. [Means for solving the problem]
[0011] The present inventors have found that by using a water-soluble thermoplastic resin and a block copolymer in combination as binder components in a conductive composition, even if the conductive composition is solidified to form a conductor, it dissolves in water and can be easily peeled off from the base substrate by washing with water, and a conductor having both the conductivity and elasticity required for a wearable device can be obtained, and a conductive composition having excellent printability and processability required for a device manufacturing process can be realized. The present invention is based on such findings. That is, the gist of the present invention is as follows.
[0012] [1] A composition comprising at least (A) a water-soluble thermoplastic resin, (B) a block copolymer, and (C) conductive particles; The block copolymer has an SP value of ±5 (J / cm 3 ) 1 / 2 The conductive composition has an SP value of [2] The conductive composition according to [1], wherein the block copolymer (B) has a hard segment block and a soft segment block. [3] The conductive composition according to [1] or [2], wherein a ratio of the water-soluble thermoplastic resin (A) to the block copolymer (B) is within a range of 15:85 to 95:5 on a mass basis. [4] The (A) water-soluble thermoplastic resin is at least one resin selected from the group consisting of polyvinyl alcohol, polyvinylpyrrolidone, polyvinyl acetal, polyethylene oxide, polyethylene glycol, polypropylene glycol, polybutylene glycol, polyoxazoline, and polyamide, and has an SP value of 12 (J / cm 3 ) 1 / 2 Above, 15(J / cm 3 ) 1 / 2 The conductive composition according to any one of [1] to [3], which is: [5] The conductive composition according to any one of [1] to [4], which is used for forming a conductor. [6] A conductor obtained by solidifying the conductive composition according to any one of [1] to [5]. [7] A laminated structure comprising a substrate and a layer made of the conductor according to [6] provided on the substrate. [8] An electronic component comprising a layer made of the conductor according to [6] or the laminated structure according to [7]. Effect of the Invention
[0013] According to the conductive composition of the present invention, by using the block copolymer (B) and the water-soluble thermoplastic resin (A) in combination as the binder components, even when the conductive composition is solidified to form a conductor, it dissolves in water and can be easily peeled off from the base substrate by washing with water, and a conductor having both the conductivity and elasticity required for a wearable device can be obtained, and a conductive composition with excellent printability and processability required for the device fabrication process can be realized. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] [Conductive composition] The conductive composition of the present invention contains (A) a water-soluble thermoplastic resin, (B) a block copolymer, and (C) conductive particles, and thus dissolves in water and can be easily peeled off from the base substrate by washing with water, and can provide a conductor that combines conductivity and elasticity. It is not necessarily clear that a conductive composition that is particularly excellent in printability and processability can be obtained by using (B) a block copolymer having an SP value close to that of (A) the water-soluble thermoplastic resin in combination, but it is presumed that this is due to the good compatibility between (A) the water-soluble thermoplastic resin and (B) the block copolymer.
[0015] The conductive composition of the present invention can be suitably used to form conductors for wearable devices such as external devices, surface devices, electronic skin devices, and internal devices, taking advantage of the above-mentioned properties, and when the device is disposed of, expensive conductors used in wiring and electrodes can be dissolved in water and easily peeled off and recovered from the base substrate. Each component contained in the conductive composition of the present invention will be described in detail below.
[0016] <(A) Water-soluble thermoplastic resin> The (A) water-soluble thermoplastic resin contained in the conductive composition according to the present invention can be any material that has water solubility and thermoplasticity at room temperature without any particular limitation. For example, water-soluble thermoplastic resins, water-soluble proteins, water-soluble block copolymers, etc. can be suitably used.
[0017] The (A) water-soluble thermoplastic resin may be any one of polyvinyl alcohol, polyvinylpyrrolidone, polyvinyl acetal, polyethylene oxide, polyethylene glycol, polypropylene glycol, polybutylene glycol, polyoxazoline, polyamide, polyacrylamide, polyacrylic acid, cellulose ether, carboxymethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, and copolymers thereof, and any one of known and commonly used resins may be used alone or in combination of two or more.
[0018] Among the above-mentioned (A) water-soluble thermoplastic resins, polyvinylpyrrolidone is preferred because it has particularly good compatibility with the (B) block copolymer described below and good solubility in organic solvents, and therefore the resulting conductive composition has excellent printability and processability, and the resulting conductor has excellent elasticity and solubility in water.
[0019] The water-soluble thermoplastic resin (A) may be a commercially available product. Examples of commercially available products include Gohsenol manufactured by Mitsubishi Chemical Corporation, Kuraray Poval and Elvanol manufactured by Kuraray Co., Ltd., PEO (polyethylene oxide) manufactured by Sumitomo Seika Chemical Co., Ltd., S-LEC manufactured by Sekisui Chemical Co., Ltd., polyvinylpyrrolidone (powder product) manufactured by Nippon Shokubai Co., Ltd., CMC (carboxymethyl cellulose) and HEC (hydroxyethyl cellulose) manufactured by Daicel FineChem Ltd., and AQ nylon (pellets) manufactured by Toray Industries, Inc.
[0020] The weight-average molecular weight of the water-soluble thermoplastic resin (A) is preferably 20,000 to 400,000, more preferably 50,000 to 300,000. When the weight-average molecular weight is 20,000 or more, the desired effects of toughness and flexibility can be obtained. When the weight-average molecular weight is 400,000 or less, the conductive composition has good viscosity, and higher printability and processability can be achieved. When the weight-average molecular weight is 50,000 or more, an excellent effect in terms of mitigation against external impact can be obtained. The weight-average molecular weight means a standard polystyrene equivalent value measured by gel permeation chromatography (GPC).
[0021] (A) The SP value of the water-soluble thermoplastic resin is 12 (J / cm 3 ) 1 / 2 Above, 15(J / cm 3 ) 1 / 2 The SP value of the water-soluble thermoplastic resin (A) is preferably 12 (J / cm 3 ) 1 / 2 By setting the SP value at 15 (J / cm2) or more, the solubility of the conductor in water is improved, and the conductor dissolves in water when washed with water, making it easier to peel off from the base substrate. In addition, the SP value of (A) water-soluble thermoplastic resin is 15 (J / cm2) or more. 3) 1 / 2 When the SP value is equal to or less than 1, the solubility in organic solvents and the compatibility with the block copolymer (B) are improved, and the conductive composition can obtain printability and processability that facilitates application to device fabrication processes. The SP value is a value calculated by the Fedors method described in Polymer Engineering and Science, February, 1974, Vol. 14, No. 2, pp. 147-154, and can be calculated by the following formula. SP value = (△H / V) 1 / 2 (where ΔH is the molar heat of vaporization (cal), V is the molar volume (cm 3 )
[0022] <(B) Block copolymer> The (B) block copolymer contained in the conductive composition according to the present invention has rubber elasticity at room temperature (25°C). Rubber elasticity means a property that can undergo reversible deformation, such as that seen in rubber-like substances, where the deformation occurs due to an external force and returns to the original shape when the external force is removed, and for example, refers to a property that does not cause breakage or plastic deformation at an elongation of 20% at room temperature. When the conductive composition contains such a (B) block copolymer, it is possible to impart elasticity to the solidified product of the conductive composition. As the block copolymer, any known and commonly used one can be used without any particular restriction as long as it has rubber elasticity at room temperature, but a block copolymer of a hard segment and a soft segment can be preferably used. The block copolymer can be used alone or in a mixture of two or more types.
[0023] The above-mentioned (B) block copolymer has low crystallinity and weak intermolecular forces, and therefore has a lower glass transition temperature (Tg) than other rubbers, is flexible and stretchable when mixed with conductive particles, and has good compatibility with (A) water-soluble thermoplastic resins and highly polar solvents such as alcohol, making it preferable. Therefore, the (B) block copolymer is suitable for forming a conductor for wearable devices, and even if the conductive composition is solidified to form a conductor, it dissolves in water and can be easily peeled off from the base substrate by washing with water, and a conductor having both the conductivity and elasticity required for wearable devices can be obtained. In particular, a block copolymer of a hard segment and a soft segment is more suitable. In this specification, the term "hard segment" refers to a segment having a glass transition temperature (Tg) of 30°C or higher, and the term "soft segment" refers to a segment having a Tg of 0°C or lower. Tg is a value measured by the starting point method in accordance with the provisions of JIS K7121. However, regarding the heating rate and temperature, the Tg observed at 40°C or higher is specifically obtained from a stabilized DSC curve obtained by repeatedly heating about 10 mg of a sample from 25°C to 200°C at a heating rate of 10°C per minute in a nitrogen gas atmosphere using a differential scanning calorimeter (DSC-6100, manufactured by Hitachi High-Tech Science Corporation). α-alumina is used as a reference. In addition, the Tg observed at less than 40°C is obtained from a stabilized DSC curve using a differential scanning calorimeter (DSC-6100, Hitachi High-Tech Science Corporation) by repeatedly heating approximately 10 mg of a sample from -100°C to 100°C at a rate of 20°C per minute under a nitrogen gas atmosphere. As mentioned above, α-alumina is used as the reference.
[0024] The ratio of the hard segment to the soft segment in the block copolymer (B) is preferably in the range of 10:90 to 70:30. If it is in this range, disconnection is unlikely to occur when the conductor obtained by solidifying the conductive composition expands and contracts, which is preferable. More preferably, it is 10:90 to 40:60.
[0025] When the hard segment is represented as an X block and an X' block and the soft segment is represented as a Y block and an Y' block, the above-mentioned block copolymer (B) may be an X block-Y block type diblock copolymer, an X block-Y block-X block type, an X block-Y block-X' block type, an Y block-X block-Y block type, or an Y block-X block-Y' block type triblock copolymer. From the viewpoint of excellent compatibility with other components and flexibility, an X block-Y block-X block type triblock copolymer is preferred.
[0026] Here, examples of the hard segment in the (B) block copolymer include methyl (meth)acrylate units and styrene units. Examples of the soft segment unit include n-butyl acrylate and butadiene units. The (B) block copolymer is preferably a triblock copolymer of polymethyl (meth)acrylate / poly n-butyl (meth)acrylate / polymethyl (meth)acrylate. Such a (B) block copolymer has excellent compatibility with the (A) water-soluble thermoplastic resin and the high polarity solvent, so that the obtained conductive composition has good fluidity and is excellent in continuous printability and processability. The (B) block copolymer may be used alone or in combination of two or more kinds. In this specification, (meth)acrylate is a term that collectively refers to acrylate and methacrylate, and the same applies to other similar expressions.
[0027] (B) The block copolymer may be a commercially available product. An example of a commercially available product is an acrylic triblock copolymer produced by living polymerization manufactured by Arkema. Specifically, SBM type represented by polystyrene-polybutadiene-polymethyl methacrylate, MAM type represented by polymethyl methacrylate-polybutyl acrylate-polymethyl methacrylate, and MAM N type or MAM A type modified with carboxylic acid or hydrophilic group can be used. Examples of SBM type are E41, E40, E21, and E20 manufactured by Arkema. Examples of MAM type are M51, M52, M53, and M22 manufactured by Arkema. Examples of MAM N type are 52N and 22N. An example of MAM A type is SM4032XM10. Another example of a commercially available product is Kuraly manufactured by Kuraray. This Kuraly is a block copolymer derived from methyl methacrylate and butyl acrylate.
[0028] The block copolymer containing the above-mentioned (meth)acrylate polymer block can be obtained, for example, by the method described in JP-A-2007-516326 or JP-A-2005-515281.
[0029] The weight-average molecular weight of the (B) block copolymer is preferably 20,000 to 400,000, more preferably 50,000 to 300,000. When the weight-average molecular weight is 20,000 or more, the desired effects of toughness and flexibility can be obtained. When the weight-average molecular weight is 400,000 or less, the conductive composition has good viscosity, and higher printability and processability can be achieved. When the weight-average molecular weight is 50,000 or more, an excellent effect in terms of mitigation against external impact can be obtained.
[0030] The tensile elongation at break of the block copolymer (B) is preferably 100 to 600% as measured by the International Organization for Standardization's international standard ISO 37:2017. When the tensile elongation at break is 100 to 600%, the conductor has better elasticity and better stability of electrical resistance. It is more preferably 300 to 600%. Tensile elongation at break (%) = (elongation at break (mm) - initial dimension (mm)) / (initial dimension (mm)) x 100
[0031] The above-mentioned (B) block copolymer has an SP value of ±5 (J / cm) relative to the SP value of the (A) water-soluble thermoplastic resin. 3 ) 1 / 2 In the present invention, the block copolymer (B) must have an SP value within ±5 (J / cm) of the SP value of the water-soluble thermoplastic resin (A). 3 ) 1 / 2 Since the conductive composition has an SP value of ±3 (J / cm), even if the conductive composition is solidified to form a conductor, it dissolves in water and can be easily peeled off from the base substrate by washing with water, and a conductor having both the conductivity and elasticity required for a wearable device can be obtained, and a conductive composition having excellent printability and processability required for the device fabrication process can be obtained. The SP value of the block copolymer (B) is within ±3 (J / cm) of the SP value of the water-soluble thermoplastic resin (A). 3 ) 1 / 2 The SP value of the block copolymer is preferably in the range of 9 (J / cm 3 ) 1 / 2 Above, 12(J / cm 3 ) 1 / 2 The SP value of the block copolymer is less than 9 (J / cm 3 ) 1 / 2 Above, 12(J / cm 3 ) 1 / 2 When the SP value is less than 100%, the compatibility of the block copolymer (B) with the water-soluble thermoplastic resin (A) and the highly polar organic solvent is further improved, and the conductive composition can obtain a fluidity that allows easy application to the device fabrication process. The SP value can be calculated in the same manner as above.
[0032] In addition, the conductive composition of the present invention may be used in combination with other organic binders, such as (A) a water-soluble thermoplastic resin and (B) a water-insoluble thermoplastic resin other than a block copolymer, within a range that does not impair the effects of the present invention.
[0033] In addition, the mass ratio of the water-soluble thermoplastic resin (A) to the block copolymer (B) is preferably 15:85 to 95:5 in terms of excellent continuous printability, and more preferably 30:70 to 80:20.
[0034] In addition, the water-soluble thermoplastic resin (A) and the block copolymer (B) may contain known additives such as softeners and plasticizers. Examples of the softeners include mineral oil-based softeners and vegetable oil-based softeners. For example, the mineral oil-based softeners include various oils such as paraffin-based process oils, naphthene-based process oils, and aromatic process oils. Examples of the vegetable oil-based softeners include castor oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, pine oil, and tall oil. Examples of the plasticizers include carboxylate esters, phosphate esters, acrylic polymers, and ionic liquids. These softeners and plasticizers may be used alone or in combination. The desired rubber elasticity and extensibility can be adjusted by the amount of the softener or plasticizer added.
[0035] <(C) Conductive particles> The conductive particles (C) used in the conductive composition of the present invention can be any conventional material used in conductive compositions, such as carbon particles such as graphite, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, metal particles such as copper particles, nickel particles, and silver particles, metal carbides such as WC, B4C, ZrC, NbC, MoC, TiC, and TaC, metal nitrides such as TiN, ZrN, and TaN, and metal silicides such as WSi2 and MoSi2. These may be used alone or in combination of two or more. Among the above-mentioned conductive particles (C), silver particles and ketjen black can be preferably used.
[0036] The shape of the (C) conductive particles is not particularly limited, and examples thereof include spherical, needle-like, oval-spherical, flake-like, scale-like, and irregular shapes.
[0037] (C) When silver powder is used as the conductive particles, it is preferable to use silver particles having an average primary particle size of 1.0 μm or less, preferably 0.1 to 1.0 μm, and an apparent porosity of 50 to 95%, preferably 60 to 95%. The average primary particle size of silver powder means the average particle size of the silver powder observed in a powder state at a magnification of 10,000 times with a scanning electron microscope, randomly extracting 10 primary particles, and measuring their particle size. The apparent porosity of silver powder is an index representing the state of an aggregate structure (secondary particles) in which the primary particles of silver powder are connected to each other to have an appropriate amount of voids, and can be measured as follows. That is, The density of silver is ρ0 (g / cm 3 )year, The volume of silver powder when a load of 1 kg is applied to silver powder with a mass of M (g) is V (cm 3 ), the apparent density ρ(g / cm 3 )teeth, ρ=M / V From the apparent density, the apparent porosity (P) can be calculated using the following formula: P = (1-ρ / ρ0) × 100 The density of silver, ρ0, is 10.49 g / cm 3 The silver powder volume V under a 1 kg heavy load is the silver powder volume 1 hour after the load is applied.
[0038] In the present invention, the shape of the primary particles of the silver powder is preferably approximately spherical. The shape of the primary particles of the silver powder is not limited to approximately spherical, and it goes without saying that silver powder having a shape other than approximately spherical may be included within a range that does not impair the effects of the present invention.
[0039] In addition, the silver powder that can be suitably used in the present invention preferably has a DBP oil absorption of 30 to 200 ml / 100 g as measured in accordance with JIS K 6217-4:2017.
[0040] In the present invention, when Ketjen black is used as the (C) conductive particle, from the viewpoints of film-forming property, conductivity, fluidity, and stability of electrical resistance against expansion and contraction deformation, it is preferable to use Ketjen black having an apparent porosity of 50 to 95%, preferably 60 to 95%, and a DBP oil absorption of 300 to 600 ml / 100 g. The apparent porosity and DBP oil absorption of Ketjen black can be measured by the same method as that for the silver powder described above.
[0041] The amount of the (C) conductive particles in the conductive composition can be in the range of 5 to 90 mass% based on the non-volatile components of the conductive composition. More specifically, when silver powder is used as the (C) conductive particles, the amount of the (C) conductive particles is preferably 50 to 90 mass% and more preferably 60 to 85 mass% based on the non-volatile components of the conductive composition. When Ketjen black is used as the (C) conductive particles, the amount of the (C) conductive particles is preferably 5 to 40 mass% and more preferably 20 to 30 mass% based on the non-volatile components of the conductive composition.
[0042] By using the conductive particles (C) having the above-described characteristics in an amount within the above-described range, it is possible to obtain a conductor that has a low initial electrical resistance before stretching, has excellent electrical resistance stability even when stretched, and can be easily peeled off by washing with water.
[0043] In the present invention, in order to adjust the affinity between the (C) conductive particles and the (A) water-soluble thermoplastic resin or the (B) block copolymer, surface-treated (C) conductive particles or a dispersant may be used. Examples of surface treatment of the (C) conductive particles include a wet method in which the (C) conductive particles are put into a solution containing a dispersant and stirred, and a dry method in which a solution containing a dispersant is sprayed onto the (C) conductive particles while stirring them. Furthermore, a surfactant may be used in combination for surface treatment. There are no particular limitations on the amount or order of blending the dispersant, but the amount of blending may be 0.01 to 30 mass% relative to the (C) conductive particles, and the order of blending may be a method in which the (B) block copolymer and the dispersant are mixed and then the (C) conductive particles are blended.
[0044] As the dispersant used in the above-mentioned surface treatment or blending, a conventionally known one can be used. For example, when the (C) conductive particles are silver powder, protective colloids such as fatty acids, organic metals, and gelatin can be used. However, in consideration of the possibility of impurities being mixed in and the improvement of the adsorption to the hydrophobic group, fatty acids or their salts are preferable. In addition, as the dispersant, fatty acids or their salts emulsified with a surfactant may be used. Specifically, fatty acids having 6 to 24 carbon atoms, such as stearic acid, oleic acid, myristic acid, palmitic acid, linoleic acid, lauric acid, and linolenic acid, can be more preferably used. These fatty acids are considered to have little adverse effect on the wiring layer and electrodes using the conductive composition. The above-mentioned fatty acids may be used alone or in combination.
[0045] Furthermore, when the (C) conductive particles are Ketjen black, the dispersant that can be suitably used may be a phosphoric acid ester having an acidic group or a basic group or both, an acrylic copolymer, a polyamine, a polyurethane, a polyester, a polyacrylate, and their phosphates, alkyl ammonium salts, etc. The above-mentioned dispersants may be used alone or in combination.
[0046] <Other ingredients> The conductive composition of the present invention may contain an organic solvent for adjusting the composition or for adjusting the viscosity for application to a substrate.
[0047] Examples of such organic solvents include ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, and petroleum-based solvents. More specifically, the organic solvents include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, diethylene glycol monoethyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, propylene glycol, butylene glycol, and terpineol; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. These organic solvents are used alone or as a mixture of two or more kinds. Among these, diethylene glycol monoethyl ether acetate and terpineol are preferred from the viewpoints of the solubility and coatability of the binder resin and the continuous printability.
[0048] The boiling point of the organic solvent used in the present invention is preferably 150° C. or higher, and more preferably 200° C. or higher. By using an organic solvent with the above boiling point, it is possible to prevent the organic solvent from volatilizing during the device production process, which would otherwise cause a decrease in the continuous printability and processability of the conductive composition.
[0049] The conductive composition of the present invention may further include a thermosetting component. Examples of the thermosetting component include polyester resins (urethane-modified, epoxy-modified, acrylic-modified, etc.) capable of forming a film by increasing the molecular weight through a curing reaction and forming crosslinks, epoxy resins, urethane resins, phenolic resins, melamine resins, vinyl resins, silicone resins, and blocked isocyanates.
[0050] The conductive composition of the present invention may contain other components within the range that does not impair the effects of the present invention. For example, it may contain additives such as a coupling agent and a photopolymerization initiator.
[0051] The conductive composition of the present invention can be produced, for example, by kneading the resin component dissolved in a solvent with the above-mentioned (C) conductive particles. As a kneading method, for example, a method using a stirring and mixing device such as a roll mill can be mentioned. Specifically, a resin solution with a solid content of 50 mass % is prepared by dissolving the resin component in an organic solvent, and the (C) conductive particles are blended into this resin solution, pre-stirred and mixed with a stirrer, and then kneaded with a three-roll mill to obtain a conductive composition. Depending on the type of resin component used and the blending ratio of the organic solvent, a liquid conductive composition or a paste-like (semi-solid) conductive composition can be produced.
[0052] The viscosity of the conductive composition of the present invention is not particularly limited, but is preferably 100 to 5000 dPa·s, and more preferably 200 to 1000 dPa·s. By setting the viscosity within this range, a conductive composition having excellent printability and processability required for device fabrication processes can be obtained.
[0053] In the present invention, the conductive composition as described above can be applied in a pattern onto a substrate and then subjected to a heat treatment to form a conductor. Examples of the heat treatment include a drying treatment and a heat curing treatment.
[0054] Thus, the conductive composition of the present invention can provide a conductor that is soluble in water, can be peeled off from the base substrate by washing with water, and has excellent elasticity and stability of electrical resistance.
[0055] <Laminated structure having a conductor and a conductor layer, and uses thereof> The conductive composition described above can be solidified to form a conductor. For example, a coating film made of the conductive composition can be formed, dried, and solidified to form a conductor layer. The conductive composition is solidified by drying or heat treating the conductive composition. Examples of heat treatment include hot air drying or heat curing. Prior to the heat treatment, molding may be performed. For example, the conductive layer can be obtained by applying the conductive composition to a substrate so as to have a desired shape, and then solidifying the composition. The conductive layer may have various shapes depending on the application. For example, the conductive layer can be suitably applied to conductor circuits and wiring.
[0056] The method for producing a conductor circuit includes a pattern forming step of printing or applying the conductive composition onto a substrate to form a coating pattern, and a step of solidifying the patterned coating. The coating pattern can be formed by a masking method, a method using a resist, or the like.
[0057] Examples of the pattern forming process include a printing method and a dispensing method. Examples of the printing method include gravure printing, offset printing, and screen printing, and when forming a fine circuit, screen printing is preferred. In addition, gravure printing and offset printing are suitable as a large-area coating method. The dispensing method is a method in which the amount of conductive composition applied is controlled to form an extrusion pattern from a needle, and is suitable for forming a partial pattern such as an earth wiring or a pattern on an uneven part.
[0058] The substrate to which the conductive composition is applied can be any electrically insulating material without any particular limitations, and examples thereof include paper-phenolic resin, paper-epoxy resin, glass cloth-epoxy resin, glass-polyimide, glass cloth / nonwoven cloth-epoxy resin, glass cloth / paper-epoxy resin, synthetic fiber-epoxy resin, copper-clad laminates of all grades (such as FR-4) using composite materials such as fluororesin, polyethylene, polyphenylene ether, and polyphenylene oxide-cyanate ester, sheets or films made of plastics such as polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate, polyimide, polyphenylene sulfide, and polyamide, sheets or films made of crosslinked rubbers such as urethane, silicone rubber, acrylic rubber, and butadiene rubber, and sheets or films made of thermoplastic elastomers such as polyesters, polyurethanes, polyolefins, and styrene block copolymers. Among these, by using not only flexible materials but also elastic materials (e.g., rubber, thermoplastic elastomers, urethane, etc.) as the substrate, the conductor can be applied to applications such as those described below. As the stretchable material, the same materials as the above-mentioned block copolymer (B) can be used.
[0059] <Laminated structure> The above-mentioned conductor can be made into a laminated structure by forming a plurality of layers. There is no particular limitation on the method of forming the laminated structure, but for example, a conductor obtained by solidifying a conductive composition may be bonded by heat, pressure, or both, or a conductive composition may be applied onto a conductor and then solidified. The laminated structure may include layers other than the above-mentioned conductor, such as a metal layer, an insulating layer, a protective layer, an adhesive layer, an adhesive layer, and a gap layer.
[0060] <Electronic components> An electronic component can be formed using the above-mentioned conductor or laminate structure as a component. There are no particular limitations on the structure, formation method, or use of the electronic component as long as the electronic component has the above-mentioned conductor or laminate structure as a component, but examples of uses include sensors, actuators, capacitors, inductors, transistors, converters, thermistors, connectors, transformers, capacitors, diodes, regulators, motors, antennas, switches, etc., and electronic components that combine a plurality of these uses may also be used.
[0061] The conductor obtained by solidifying the conductive composition according to the present invention has excellent stability of electrical resistance even when repeatedly stretched or stretched as described above, and therefore can be suitably used for forming conductors for wearable devices such as external devices, body surface devices, electronic skin devices, and internal devices, in addition to conductor circuits and wiring. The conductor layer can also be applied to electrodes of flexible printed circuit boards. Furthermore, the conductive composition of the present invention is also suitable for forming conductor layers such as actuator electrodes. In addition, since the formed conductor can be dissolved in water, it can be peeled off from the base substrate by washing with water. Therefore, when disposing of the device, the expensive (C) conductive particles can be easily recovered, which is economically rational and has a small environmental impact. In addition, it is also suitable for forming conductors with designs that were previously difficult to realize due to insufficient stretchability and stability of electrical resistance. For example, the following can be mentioned.
[0062] <Wearable biosensor> The conductor of the present invention can be applied as a wiring material for a wearable biosensor that is worn to acquire and transmit action potentials / biological information generated by animals and plants, including humans. The sensor must be attached to a location that is in close contact with or close to the surface tissue of animals and plants, including humans, but the surface tissue expands and contracts. Conventional hard and flexible substrates cannot follow the expanding and contracting attachment location, and the location where the sensor can be attached is limited, resulting in limited biological information. According to the conductor of the present invention, the sensor wiring material can be applied to the surface tissue of animals and plants, including humans, so that a wearable biosensor can be made that can be attached to a location where expansion and contraction occurs.
[0063] The wiring used in wearable biosensors can be formed by screen printing or dispensing methods, which makes it possible to miniaturize signal wiring, which is thought to contribute to the miniaturization of sensor devices.
[0064] <Wiring material for smart textiles> In recent years, the field of so-called "smart textiles" using woven fabrics as sensors is expanding. A wiring board or sensor in which wiring is formed on a stretchable substrate that can be thermocompressed using the conductor of the present invention has excellent stability of electrical resistance when stretched, so that by attaching it to the surface of a stretchable woven fabric, it is possible to develop a woven fabric with electronic device functions, i.e., a smart textile. As a smart textile, functions such as pressure-sensitive sensors, touch sensors, and antenna wiring can be imparted to the woven fabric.
[0065] <Wiring for 3D molded products> In conventional plastic molded products for electronic device housings and the like made by the FIM (Film Insert Molding) method, a plastic film such as polycarbonate is used as the base material, which is printed with a design and then heat-pressed. The conductor wiring of the present invention, which is made of a laminated structure in which the conductor is provided on an elastic substrate, has the characteristics of being free from disconnection when stretched and suppressing changes in resistance value, so that the conductor wiring can be formed during design printing of the plastic molded product, and then molding is performed by heat pressing (which causes partial stretching) to realize electronic devices with built-in 3D wiring.
[0066] In addition, by performing a heat press process using a stretchable base material such as the block copolymer (B) described above, it is possible to realize a stretchable electronics device having soft wiring in a soft housing. This can be suitably used as a pressure sensor, a touch sensor, or an antenna wiring.
[0067] <Stretchable and deformable wiring sheet or wiring board> The conductor wiring made of a laminated structure having a conductor layer of the present invention provided on an elastic substrate can be used as a wiring board sheet that can be stretched and deformed. For example, such a conductor wiring can be attached to the surface of an object having a three-dimensional shape such as a molded product while being stretched or deformed without causing disconnection of the wiring. Therefore, the laminated structure having a conductor layer of the present invention provided on an elastic substrate can be suitably used for pressure-sensitive sensors, touch sensors, or antenna wiring.
[0068] <Flexible wiring sheet or wiring board> In flexible wiring sheets or wiring boards using conventional conductive pastes, when extreme bending such as bending with a fingernail occurs, the wiring breaks. In this respect, when the conductor of the present invention is used, since it is a conductive material with elongation properties, it can accommodate bending in areas that could not be handled with conventional conductive pastes, and it is possible to realize a flexible wiring sheet or wiring board in which the wiring does not break even when bending with a fingernail. EXAMPLES
[0069] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0070] <(A) Preparation of water-soluble thermoplastic resin> The following two types of water-soluble thermoplastic resin (A) were prepared for preparing the conductive composition. Resin A: Polyvinylpyrrolidone (Polyvinylpyrrolidone K-30, manufactured by Nippon Shokubai Co., Ltd., SP value 13 (J / cm 3 ) 1 / 2 , weight average molecular weight 100,000) Resin B: Polyethylene oxide (PEO-1, manufactured by Sumitomo Seika Chemicals Co., Ltd., SP value 13 (J / cm 3 ) 1 / 2 , weight average molecular weight 200,000) Each resin was dissolved in Terpineol C manufactured by Nippon Terpen Co., Ltd. or water to prepare a resin solution with a solid content of 33 mass %. The weight average molecular weight of each resin was measured by the GPC method (polystyrene standard). For comparison, a water-soluble thermosetting resin (Shonol BRL-149, manufactured by Aica Kogyo Co., Ltd., SP value 12 (J / cm 3 ) 1 / 2 ) was prepared.
[0071] <(B) Preparation of block copolymer> As the block copolymer (B) for preparing the conductive composition, the following was prepared. Block copolymer: acrylic block copolymer (M52 manufactured by Arkema, SP value 10 (J / cm 3 )) 1 / 2 , weight average molecular weight 50,000) The above block copolymer was dissolved in diethylene glycol monoethyl ether acetate to prepare a resin solution so that the solid content was 50% by mass. For comparison, at room temperature, an amorphous polyester polyol which is a non-block copolymer (Vylon-290 manufactured by Toyobo Co., Ltd., SP value 11 (J / cm 3 )) 1 / 2 , weight average molecular weight 50,000, Tg = 72 °C) was prepared. The weight average molecular weights of the block copolymer and the non-block copolymer were measured by the GPC method (polystyrene standard).
[0072] <Calculation of SP value> The SP values of the above resin A, B, water-soluble thermosetting resin, block copolymer, and amorphous polyester polyol are values calculated by the Fedors method described in Polymer Engineering and Science, February, 1974, Vol. 14, No. 2, 147~154P, and were calculated by the following formula. SP value = (△H / V) 1 / 2 (In the formula, ΔH represents the molar heat of vaporization (cal), and V represents the molar volume (cm 3 ).) The absolute value (ΔSP value) of the difference in SP values between the above (A) water-soluble thermoplastic resin and (B) block copolymer was as shown in Table 1 below.
[0073] <Preparation of (C) conductive particles> As (C) conductive particles for preparing the conductive composition, the following two kinds of conductive particles were prepared. Conductive particle A: silver powder (Silverst AgC-G manufactured by Fukuda Metal Foil & Powder Co., Ltd., average primary particle diameter 0.5 μm, apparent porosity 83%, DBP oil absorption 90 ml / 100 g) Conductive particle B: Carbon black (EC300J, manufactured by Lion Specialty Chemicals Co., Ltd., average primary particle diameter 39.5 μm, apparent porosity 91%, DBP oil absorption 360 ml / 100 g)
[0074] The average primary particle diameter of each of the conductive particles A and B was obtained by observing the particles with a scanning electron microscope at a magnification of 10,000 times, randomly extracting 10 primary particles, measuring their particle diameters, and calculating the average value. The apparent porosity was calculated by setting the density ρ0 of the conductive particle A to 10.49 g / cm. 3 , the density of conductive particle B is 2.2 g / cm 3 and calculated from the above formula: P = (1 - ρ / ρ0) × 100. Furthermore, the DBP oil absorption was measured in accordance with JIS K 6217-4:2017.
[0075] <Preparation of Conductive Composition> The above-mentioned (C) conductive particles and each resin solution were mixed according to the composition shown in Table 1 below, pre-mixed with a mixer, and then mixed with a three-roll mill (EXAKT50, manufactured by EXAKT) while varying the conditions such as the number of times of mixing, the rotation speed, and the roll interval of the three-roll mill, to obtain a conductive composition according to the embodiment. The numerical values of the blending amounts in Table 1 represent parts by mass converted into solid content.
[0076] <Evaluation of Conductive Composition> (1) Measurement of continuous printability Each conductive composition was applied to a PET film substrate (Lumirror, manufactured by Toray Industries, Inc.) by screen printing, and the number of sheets that could be continuously printed was measured. Continuous printability was evaluated based on the following evaluation criteria. ◎: Continuous printing of 100 or more sheets is possible ○: Continuous printing of 10 or more but less than 100 sheets is possible ×: Separation of resin components, clogging of plate, conductive composition repellency, etc. occur, making printing impossible The evaluation results are shown in Table 1.
[0077] (2) Resistivity measurement Each conductive composition was applied to a substrate by screen printing and heat-treated at 80°C for 30 minutes to obtain a conductor. A PET film (Lumirror, manufactured by Toray Industries, Inc.) was used as the substrate. The resistance value at both ends of the obtained conductor was measured by the four-terminal method, and further the line width, line length and thickness were measured to obtain the specific resistance (volume resistivity). The measurement results are shown in Table 1. Note that in cases where a conductor could not be formed and measurements could not be made because the conductive composition was repelled by the screen or the conductive composition dried during printing and caused clogging of the screen, etc., the mark * was entered.
[0078] (3) Elasticity measurement Each conductive composition was applied to a substrate by screen printing and heat-treated at 80°C for 30 minutes to form a conductor with a line width of 1 mm, a thickness of 20 μm, and a length of 40 mm on the substrate. A urethane substrate with an elastic modulus of 30 MPa (manufactured by Okura Kogyo Co., Ltd., ES85, thickness 100 μm) was used as the substrate. The substrate on which the conductor was formed was stretched to an elongation of 20% at a speed of 5 mm / sec, and then held in that state for 15 seconds. The resistivity (volume resistivity) of the conductor was measured, and the conductivity of the conductor when stretched was evaluated based on the following evaluation criteria. ◎: The resistivity when stretched by 20% is 10 times or less than the initial value (when not stretched) ○: The resistivity at 20% elongation is more than 10 times and less than 100 times the initial value (at non-elongation). ×: The resistivity at 20% stretch is more than 100 times the initial value (at non-stretch) (including breaks) The evaluation results are shown in Table 1. In addition, when a conductor could not be formed and measurement was not possible due to reasons such as the conductive composition being repelled by the screen or the conductive composition drying during printing causing clogging of the screen, the result is marked with *.
[0079] (4) Measurement of solubility in water Each conductive composition was applied to a substrate by screen printing and heat-treated at 80°C for 30 minutes to obtain a conductor. A PET film (Lumirror, manufactured by Toray Industries, Inc.) was used as the substrate. The obtained conductor was immersed in 40°C water for 30 seconds, and the state of change was visually observed. The solubility of the conductor in water was evaluated based on the following evaluation criteria. ◎: Conductor naturally disintegrates ○: After the test, the conductor collapses when touched with a finger. ×: Conductive material remains even when touched with a finger after testing The evaluation results are shown in Table 1. In addition, when a conductor could not be formed and measurement was not possible due to reasons such as the conductive composition being repelled by the screen or the conductive composition drying during printing causing clogging of the screen, the result is marked with *.
[0080] [Table 1]
[0081] As is clear from the results shown in Table 1, the conductive compositions (Examples 1 to 6) containing (A) a water-soluble thermoplastic resin, (B) a block copolymer, and (C) conductive particles are soluble in water and can be easily peeled off from the base substrate by washing with water, and can provide conductors that combine the conductivity and elasticity required for wearable devices.It is also clear that the conductive compositions have excellent compatibility with each other and therefore have excellent continuous printability, which is required for the manufacturing process.
[0082] On the other hand, in the conductive composition using a non-block copolymer instead of the (B) block copolymer (Comparative Example 1), it is presumed that the compatibility between the (A) water-soluble thermoplastic resin and the non-block copolymer is low, and it is understood that this is not suitable for preparing a conductive composition. In addition, it is understood that the conductive compositions containing only either the (A) water-soluble thermoplastic resin or the (B) block copolymer as a binder (Comparative Examples 2 and 3) cannot achieve both the elasticity and solubility of the conductor. In addition, it is understood that the conductive composition containing a water-soluble thermosetting resin instead of the (A) water-soluble thermoplastic resin (Comparative Example 4) cannot obtain the elasticity and solubility of the conductor.
Claims
1. (A) a water-soluble thermoplastic resin (excluding (B) a block copolymer), (B) a block copolymer, and (C) a conductive particle; The block copolymer (B) has an SP value of ±5 (J / cm) relative to the SP value of the water-soluble thermoplastic resin (A). 3 ) 1/2 and having an SP value of the ratio of the water-soluble thermoplastic resin (A) to the block copolymer (B) is in the range of 15:85 to 95:5 on a mass basis, The conductive composition, wherein the blending amount of the conductive particles (C) is in the range of 5 to 90 mass % based on the non-volatile components of the conductive composition.
2. The conductive composition according to claim 1 , wherein the block copolymer (B) has a hard segment block and a soft segment block.
Citation Information
Patent Citations
Conductive polymer composition and conductive component using it
JP1999181311A
Resin composition containing water-absorptive resin and adhesive comprising the resin composition as effective component
JP2002167520A
Electroconductive thermoplastic resin composition, method for producing the same, and injection-molded resin article and extrusion-molded article obtained therefrom
JP2010270308A
Conductive composition, conductive body using the same, and laminate structure
JP2020132756A
Conductive composition and conductor including the same, laminate structure and electronic component
JP2022047973A